STEAM Based Activities Through Problem Solving in Early Childhood - Qorina Widadiyah; Novi Hidayati; Fitri Meliani (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2026)
This research is motivated by the fact that children have not been able to pour their imagination and critical thinking skills into concrete objects. The purpose of this study is to enhance children's problem-solving abilities using the STEAM method. The research method used PTK (Classroom action research) with a qualitative approach, and 2 cycles were carried out. Data collection techniques use observation and documentation. The research procedure involves planning, implementing, observing, and reflecting. The data analysis is carried out using percentages on a Likert scale, adjusted to the indicators studied. The results of the study indicate that the success of this study can be seen in cycle 1: 58% have not developed, 78% are starting to develop, and 16% are developing as expected. Improvements are seen in cycle II, namely developing as expected by up to 39% and developing very well by up to 73%, who previously had not been able to develop further. This can occur through children's activities using a digital storybook entitled "Gara-Gara Piko", which describes activities that help children imagine ways to solve the problems it contains. Then the child realizes it by drawing on a piece of paper, inspired by the storybook they have heard previously.